2008
DOI: 10.2134/agronj2007.0229
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Use Efficiency and Nitrogen Uptake of juncea Canola under Diverse Environments

Abstract: A gronomy J our n al • Volume 10 0 , I s sue 2 • 2 0 0 8 285 ABSTRACT Nitrogen accounts for the largest energy input in oilseed production. Understanding N use characteristics of oilseed crops will help improve N use effi ciency and minimize production costs. Th is study determined nitrogen use effi ciency (NUE, defi ned as seed yield produced per unit of N supply), nitrogen fertilizer use effi ciency (NFUE, defi ned as seed yield produced per unit of fertilizer N), and crop N uptake for oilseed crops under di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
30
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 20 publications
7
30
1
Order By: Relevance
“…Therefore, similar to grain yield, to obtain maximum value of oil and protein yields, irrigation of canola plants with 450 mm ha −1 total water at the duration of growing season and fertilization with 120 kg N ha −1 could be beneficial. These results are in agreement with previous reports (Leilah and Al‐Khateeb, 2003; Al‐Barrak, 2006; Gan et al, 2008).…”
Section: Resultssupporting
confidence: 94%
See 4 more Smart Citations
“…Therefore, similar to grain yield, to obtain maximum value of oil and protein yields, irrigation of canola plants with 450 mm ha −1 total water at the duration of growing season and fertilization with 120 kg N ha −1 could be beneficial. These results are in agreement with previous reports (Leilah and Al‐Khateeb, 2003; Al‐Barrak, 2006; Gan et al, 2008).…”
Section: Resultssupporting
confidence: 94%
“…A direct relationship between N uptake and percent seed protein is reported because of the finding that higher seed protein was correlated with higher N concentration in all vegetative parts of the plants (Zlatko and Zdenko, 2006). Nitrogen concentration in High‐N was consistently higher than in Low‐N, which is in accordance with the results presented here (Zlatko and Zdenko, 2006; Gan et al, 2008). These results indicated that only N rates had significant effect ( p < 0.01) on straw N concentration (Table 2), with averages 2.88 and 6.27 g kg −1 for NR 1 (control) and NR 5 (160 kg N ha −1 ) treatments, respectively.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations